INTEGRITY OF THE WORD TAWHEED AND FETO PARALLEL STATE STRUCTURING - Abdullah NAMLI (Fırat University, 2021)
Islam is known for its monotheism. The Word Tawheed consists of two sentences. The first one expresses a uniqueness of Allah. The second sentence contains the name of the prophet to be believed. Muslims must believe in all the prophets sent by Allah. Although the Word Tawheeds used in the previous prophets were valid, they lost their qualifications after the notification of the last prophet Muhammad. Like some words and sentences, The Word Tawheed can also be shortened. The use of the Word Tawheed in abbreviation has been misinterpreted in a way that deliberately serves its own purposes by some organizations that want to conduct dialogue studies interreligious dialog. Said Okur is someone who talks about the need to be allied with Christians. According to him, Dajjal is communism, which he calls northern draft. For this reason, he claimed that Christianity was returning to its origin and that it was necessary to make an alliance with them. One of the organizations established by taking advantage of Said Okur's views and distorting some of his views is the “Parallel State Structure of Fetö. Initially, the Vatican's demands for dialogue were met by the Presidency of Religious Affairs and some theological faculties. However, the Fetö organization has taken advantage of the lack of coordination of official institutions and has been involved in dialogue activities by highlighting some of the social and material opportunities it has. The leader and sympathizers of the Fetö terrorist organization immediately took ownership of the interfaith dialogue work belonging to the Vatican Church when they found it appropriate. They have tried to change some Islamic principles that they do not consider appropriate for interfaith dialogue work or to make them appropriate for dialogue activity. The most important of these is that they have put forward deliberate, false views claiming that the second half of The Word Tawheed is not necessary, which means even though Muhammad is not believed, one can be on the right path.